Single center experience and early outcomes of Impella 5.5 - Funamoto, Masaki; Kunavarapu, Chandra; Kwan, Michael D.; Matsuzaki, Yuichi; Shah, Mahek; Ono, Masahiro (Frontiers in Cardiovascular Medicine, 2023)
Background Acute decompensated heart failure (HF) and cardiogenic shock (CS) frequently are refractory to conservative treatment and require mechanical circulatory support (MCS). We report our early clinical experience and evaluate patient outcomes with the newer generation surgical Impella 5.5. Methods Seventy patients that underwent Impella 5.5 implantation between October 2019 and December 2021 at a single center were enrolled in this study. Pre-operative characteristics, peri-operative clinical course information, and post-operative outcomes were retrospectively collected. Results Fifty-seven (81%) patients survived to discharge, and 51 (76%) patients survived at the time of the first 30 days post-discharge visit. Thirty-one patients (44%) received Impella support for a bridge to advanced surgical heart failure therapy (transplant or durable left ventricular assist device (LVAD)), 27 (39%) cases were used for a bridge to recovery/decision and 12 (17.1%) cases was used for planned perioperative support for high-risk cardiac surgery procedure. Conclusions Our results suggest that Impella 5.5 provides favorable survival in the management of HF and CS, particularly used for a bridge to heart transplant or LVAD. Early extubation and mobilization with high flow circulatory support allowed effective tailoring of MCS approaches from peri-operative support for high-risk cardiac surgery, bridge to recovery, and to advanced surgical heart failure therapy.